Bioeconomic Appraisal of Marigold under Mangifera indica Based Agroforestry System in Submontane and Low Hill Subtropical Zone of Himachal Pradesh - Chauhan, Sahil; Guleria, Vipan; Sharma, Prem Prakash; Divyanshu; Vashishat, Rohit (International Journal of Economic Plants, 2024)
The experiment was conducted during the month of October–March in the year 2020–2021. The bio-economic appraisal of marigold study primarily focused on land use options as a means to ensure sustainable livelihood security. The experiment was laid out in randomized block design (factorial) with nine treatments i.e. FYM, Nitrogen and no manure with nine organic manure doses and control with three trees spacing viz., (Sp1)–2×2 m2, (Sp2)–2.5×2.5 m2, (Sp3)–3×3 m2 under Mangifera indica based agroforestry system. The results in general indicated that the overall net returns were found to be the maximum of 7.18 lakh ha-1 in (Sp1)–2×2 m2 tree spacing and highest B:C ratio (5.34) was observed in the application of T2:FYM 40 t ha-1+Nitrogen 400 kg dose to the marigold as under crop. Monocropping neither provides gainful employment opportunity nor generates sufficient income to meet the family expenses. This study aims at evaluating the performance of Mangifera indica based agroforestry in terms of income, employment and environmental impact from the farmers’ perspective. Mangifera indica – based agroforestry is economically important and more profitable than many of the crop rotations followed in the lower hill regions. This land-use system is also capable of providing employment opportunities on farms. Improvement in marigold yield and higher economic returns indicated that combination of Mangifera indica and marigold can be a viable option for farmers of subtropical areas of Himachal Pradesh for the upliftment of their socioeconomic status. In comparison to traditionally grown wheat crop, flower annuals were found profitable under Mangifera indica fruit-based system.